Tire

The tire incorporates an ethylene-anisylpropylene copolymer in its rubber composition to enhance self-repairability and crack growth resistance, addressing the challenges of durability and environmental considerations.

JP2025056583APending Publication Date: 2025-04-08SUMITOMO RUBBER INDUSTRIES LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023166154
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Tires face challenges in achieving durability and environmental considerations, particularly in terms of crack growth resistance and self-repairability.

Method used

A tire composed of a rubber composition containing a rubber component and an ethylene-anisylpropylene copolymer, where the copolymer is a block copolymer with soft segments made of alternately connected ethylene and anisylpropylene, and hard segments of polyethylene, with a number average molecular weight between 3,000 and 700,000, and a content ratio satisfying the equation (1) Content of the rubber component / Content of the copolymer > 1.0.

Benefits of technology

The tire exhibits self-repairability and excellent crack growth resistance due to the intertwining of soft segments and the regeneration of hard segments, dispersing stress through sacrificial bonds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056583000006
    Figure 2025056583000006
  • Figure 2025056583000007
    Figure 2025056583000007
  • Figure 2025056583000008
    Figure 2025056583000008
Patent Text Reader

Abstract

To provide a tire having self-healing properties and excellent crack growth resistance.SOLUTION: There is provided a tire having a tire member composed of a rubber composition comprising a rubber component and an ethylene-anisylpropylene copolymer, wherein the copolymer is a block copolymer comprising a soft segment block and a hard segment block, the soft segment is formed by alternately combining ethylene and anisylpropylene and the total ratio of the structural units of the soft segment is 60 mol% or more of the total structural units of the copolymer, the hard segment consists of a polyethylene and the copolymer has a number average molecular weight of 3000 or more and 700000 or less and satisfies the following expression (1). The content [mass%] of the rubber component in the rubber composition / the content [mass%] of the copolymer in the rubber composition>1.0 (1).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tire. [Background technology]

[0002] Recently, from the viewpoint of environmental considerations, etc., tires are required to have higher performance such as durability, and in particular, improved resistance to crack growth is desired. Summary of the Invention [Problem to be solved by the invention]

[0003] An object of the present invention is to solve the above problems and to provide a tire that has self-repairing properties and excellent crack growth resistance. [Means for solving the problem]

[0004] The present invention provides a tire having a tire member made of a rubber composition containing a rubber component and an ethylene-anisylpropylene copolymer, The copolymer is a block copolymer consisting of a soft segment block and a hard segment block, The soft segment is composed of alternating ethylene and anisylpropylene, the total proportion of the structural units of the soft segment accounts for 60 mol % or more of the total structural units of the copolymer, The hard segment is made of polyethylene, The copolymer has a number average molecular weight of 3,000 or more and 700,000 or less, The present invention relates to a tire that satisfies the following formula (1): The content of the rubber component in the rubber composition [mass%] / the content of the copolymer in the rubber composition [mass%] > 1.0 (1) Effect of the Invention

[0005] The present invention provides a tire having a tire component made of a rubber composition containing a rubber component and an ethylene-anisylpropylene copolymer, the copolymer being a block copolymer made of a soft segment block and a hard segment block, the soft segment being composed of ethylene and anisylpropylene linked alternately, and the total proportion of the structural units of the soft segment accounting for 60 mol % or more of the total structural units of the copolymer, the hard segment being composed of polyethylene, the copolymer having a number average molecular weight of 3,000 or more and 700,000 or less, and satisfying formula (1), thereby providing a tire having self-repairing properties and excellent crack growth resistance. [Brief description of the drawings]

[0006] [Figure 1] 1 is a cross-sectional view showing a portion of a pneumatic tire. [Diagram 2] FIG. 2 is an enlarged cross-sectional view showing the vicinity of the tread of the tire of FIG. 1. [Diagram 3] FIG. 2 is a diagram showing the structure of a metallocene complex used in the examples. [Figure 4] FIG. 1 shows structures of anisylpropylenes used in the examples. [Diagram 5] FIG. 1 shows the analytical values ​​and 1H NMR spectrum of polymer P1 obtained in Run 1 in Table 1. [Figure 6] FIG. 1 shows the 13C NMR spectrum of polymer P1 obtained in Run 1 in Table 1. [Figure 7] FIG. 1 shows analytical values ​​and a partially enlarged view of the 13C NMR spectrum of polymer P1 obtained in Run 1 in Table 1. [Figure 8] FIG. 1 shows a DSC curve of polymer P1 obtained in Run 1 in Table 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The present invention relates to a tire having a tire member made of a rubber composition containing a rubber component and an ethylene-anisylpropylene copolymer, the copolymer being a block copolymer made of a soft segment block and a hard segment block, the soft segment being composed of ethylene and anisylpropylene linked alternately, and the total proportion of the structural units of the soft segment being 60 mol % or more of the total structural units of the copolymer, the hard segment being composed of polyethylene, and the copolymer having a number average molecular weight of 3,000 or more and 700,000 or less, satisfying the formula (1).

[0008] The mechanism (reason) by which the above-mentioned tire provides the above-mentioned effects is not entirely clear, but is presumed to be as follows. When a relatively small amount of the specific ethylene-anisylpropylene copolymer is blended with the rubber component so as to satisfy the relational formula (1), an island phase of the copolymer is formed in the sea phase of the rubber. Then, the soft segments of the copolymer are entangled and the hard segments are regenerated, resulting in self-repairing properties. When stress is applied, the domains of the copolymer act as sacrificial bonds to disperse the stress. Therefore, it is presumed that self-repairing properties are imparted and crack growth resistance is improved.

[0009] In this way, the present invention solves the problem (objective) of imparting self-repairing properties and improving crack growth resistance by compounding the specific ethylene-anisylpropylene copolymer in a composition that satisfies the relationship "content [mass%] of the rubber in the rubber composition / content [mass%] of the copolymer in the rubber composition>1.0 (1)". In other words, the parameters in the above formula (1) do not define the problem (objective), and the problem of the present application is to impart self-repairing properties and improve crack growth resistance, and a composition that satisfies the parameters is used as a means to solve the problem.

[0010] The tire of the present invention has a tire component made of a rubber composition. The chemicals that can be used for the rubber composition will be described below.

[0011] The rubber composition includes a rubber component. Here, the rubber component is a component that contributes to crosslinking, and generally corresponds to a polymer with a weight average molecular weight (Mw) of 10,000 or more, which is not extracted with acetone. The rubber component is in a solid state at room temperature (25°C).

[0012] The weight average molecular weight of the rubber component is preferably 50,000 or more, more preferably 150,000 or more, even more preferably 200,000 or more, and particularly preferably 270,000 or more, and is preferably 2,000,000 or less, more preferably 1,500,000 or less, and even more preferably 1,000,000 or less. Within the above ranges, the effect tends to be better obtained.

[0013] In this specification, the weight average molecular weight (Mw) can be determined by converting it into standard polystyrene based on the measured value by gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMULTIPORE HZ-M manufactured by Tosoh Corporation). In the case of a polymer having a modifying group, the modifying group interacts with the silica gel of the column, making it impossible to obtain an accurate Mw, so that the Mw is measured before carrying out the modification treatment.

[0014] The rubber component usable in the rubber composition may be either a non-modified rubber or a modified rubber. The modified rubber may be a rubber having a functional group that interacts with a filler such as silica. For example, the modified rubber may be a terminal modified rubber (terminal modified rubber having the functional group at the terminal) in which at least one terminal of the rubber is modified with a compound (modifier) ​​having the functional group, a main chain modified rubber having the functional group at the main chain, a main chain terminal modified rubber having the functional group at the main chain and terminal (for example, a main chain terminal modified rubber having the functional group at the main chain and at least one terminal modified with the modifier), or a terminal modified rubber modified (coupled) with a polyfunctional compound having two or more epoxy groups in the molecule and having a hydroxyl group or an epoxy group introduced therein.

[0015] Examples of the functional group include an amino group, an amide group, a silyl group, an alkoxysilyl group, an isocyanate group, an imino group, an imidazole group, a urea group, an ether group, a carbonyl group, an oxycarbonyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, a thiocarbonyl group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, and an epoxy group. These functional groups may have a substituent. Among them, an amino group (preferably an amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms), an alkoxy group (preferably an alkoxy group having 1 to 6 carbon atoms), and an alkoxysilyl group (preferably an alkoxysilyl group having 1 to 6 carbon atoms) are preferred.

[0016] Examples of the rubber component include diene rubber. Examples of the diene rubber include isoprene rubber, butadiene rubber (BR), styrene butadiene rubber (SBR), styrene isoprene butadiene rubber (SIBR), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), and acrylonitrile butadiene rubber (NBR). Examples of the rubber component include butyl rubber and fluororubber. These may be used alone or in combination of two or more. These rubber components may be modified or hydrogenated, and extended rubber extended by oil, resin, liquid rubber component, or the like may be used. Among these, it is preferable to include at least one of isoprene rubber, BR, and SBR, and it is more preferable to include at least SBR.

[0017] Examples of isoprene-based rubber include natural rubber (NR), isoprene rubber (IR), modified NR, modified NR, and modified IR. Examples of NR include SIR20, RSS♯3, TSR20, and other rubber industry-standard rubbers. Examples of IR include IR2200 and other rubber industry-standard rubbers. Examples of modified NR include deproteinized natural rubber (DPNR), high-purity natural rubber (UPNR), and other rubbers. Examples of modified NR include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber. Examples of modified IR include epoxidized isoprene rubber, hydrogenated isoprene rubber, and grafted isoprene rubber. These may be used alone or in combination of two or more.

[0018] When the rubber composition contains an isoprene-based rubber, the content of the isoprene-based rubber in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. Within the above ranges, the effect tends to be better obtained.

[0019] The BR is not particularly limited, and for example, high cis BR with a high cis content, BR containing syndiotactic polybutadiene crystals, BR synthesized using a rare earth catalyst (rare earth BR), etc. can be used. These may be used alone or in combination of two or more. In particular, the BR preferably contains high cis BR with a cis content of 90% by mass or more. The cis content is more preferably 95% by mass or more. The cis content can be measured by infrared absorption spectroscopy.

[0020] The cis amount of BR means the cis amount of the BR when there is one type of BR, and means the average cis amount when there are multiple types of BR. The average cis content of BR can be calculated by {Σ(content of each BR × cis content of each BR)} / total content of all BRs. For example, when 100% by mass of the rubber component contains 20% by mass of BR with a cis content of 90% by mass and 10% by mass of BR with a cis content of 40% by mass, the average cis content of BR is 73.3% by mass (=(20×90+10×40) / (20+10)).

[0021] In addition, either unmodified or modified BR can be used as the BR. Modified BR includes modified BR in which the same functional group as that of modified rubber is introduced. In addition, hydrogenated butadiene polymer (hydrogenated BR) can also be used as the BR.

[0022] As the BR, for example, products from Ube Industries, Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, etc. can be used.

[0023] When the rubber composition contains BR, the content of BR in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. Within the above ranges, the effect tends to be better obtained.

[0024] The SBR is not particularly limited, and for example, emulsion polymerized styrene butadiene rubber (E-SBR), solution polymerized styrene butadiene rubber (S-SBR), etc. can be used. These may be used alone or in combination of two or more kinds.

[0025] The styrene content of SBR is preferably 5% by mass or more, more preferably 20% by mass or more, and even more preferably 24% by mass or more. The styrene content is preferably 60% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less. Within the above range, the effect tends to be better obtained. In this specification, the styrene content is 1 It can be measured by H-NMR measurement.

[0026] The styrene amount of SBR means the styrene amount of the SBR when there is one type of SBR, and means the average styrene amount when there are multiple types of SBR. The average styrene amount of SBR can be calculated by {Σ(content of each SBR × styrene amount of each SBR)} / total content of all SBRs. For example, when 100% by mass of the rubber component contains 85% by mass of SBR with a styrene amount of 40% by mass and 5% by mass of SBR with a styrene amount of 25% by mass, the average styrene amount of the SBR is 39.2% by mass (=(85×40+5×25) / (85+5)).

[0027] The vinyl bond content of SBR is preferably 3% by mass or more, more preferably 10% by mass or more, and even more preferably 17% by mass or more. When the vinyl bond content is within the above range of preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, the effect tends to be better. In this specification, the vinyl bond amount (1,2-bonded butadiene unit amount) can be measured by infrared absorption spectroscopy.

[0028] The vinyl content of SBR (amount of 1,2-bonded butadiene units) is the proportion of vinyl bonds when the total mass of the butadiene parts in SBR is taken as 100 (unit: mass%), and is calculated as vinyl content [mass%] + cis content [mass%] + trans content [mass%] = 100 [mass%]. When there is one type of SBR, it means the vinyl content of that SBR, and when there are multiple types, it means the average vinyl content. The average vinyl content of SBR can be calculated by Σ{content of each SBR × (100 [mass%] - styrene content of each SBR [mass%]) × vinyl content of each SBR [mass%]} / Σ{content of each SBR × (100 [mass%] - styrene content of each SBR [mass%])}. For example, in 100 parts by mass of the rubber component, there are 75 parts by mass of SBR with a styrene content of 40 mass% and a vinyl content of 30 mass%, 25 parts by mass of styrene, and 10 parts by mass of vinyl. In the case where SBR with a vinyl content of 20 mass% is 15 parts by mass and the remaining 10 parts by mass is a component other than SBR, the average vinyl content of the SBR is 28 mass% (={75 × (100 [mass%] - 40 [mass%]) × 30 [mass%] + 15 × (100 [mass%] - 25 [mass%]) × 20 [mass%])} / {75 × (100 [mass%] - 40 [mass%]) + 15 × (100 [mass%] - 25 [mass%])}.

[0029] Both unmodified and modified SBR can be used. Modified SBR includes modified SBR with the same functional groups as modified rubber. Hydrogenated styrene-butadiene copolymer (hydrogenated SBR) can also be used as SBR.

[0030] As the SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, etc. can be used. In addition, SBR synthesized by a known method can also be used.

[0031] When the rubber composition contains SBR, the content of SBR in 100% by mass of the rubber component is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and may be 100% by mass. When it is within the above range, the effect tends to be better obtained.

[0032] The rubber composition includes an ethylene-anisylpropylene copolymer, which is a block copolymer consisting of a soft segment block and a hard segment block, and the soft segments are composed of alternating ethylene and anisylpropylene, and the total proportion of the structural units of the soft segments accounts for 60 mol% or more of the total structural units of the copolymer. The hard segments are composed of polyethylene, and the ethylene-anisylpropylene copolymer has a number average molecular weight of 3,000 or more and 700,000 or less.

[0033] The method for producing the ethylene-anisilpropylene copolymer will now be described.

[0034] The ethylene-anisylpropylene copolymer is obtained by, for example, copolymerizing ethylene and at least one anisylpropylene compound with a catalyst composition containing a metallocene complex and an ionic compound. The ethylene-anisylpropylene copolymer may be copolymerized with a monomer other than ethylene and anisylpropylene compounds.

[0035] Metallocene complexes can include, but are not limited to, scandium complexes such as (C5Me4SiMe3)Sc(CH2C6H4NMe2-o)2.

[0036] Metallocene complexes can be prepared by known methods, for example, (1) X. Li, M. Nishiura, K. Mori, T. Mashiko, Z. Hou, Chem. Commun. 4137-4139 (2007), (2) M. Nishiura, J. Baldamus, T. Shima, K. Mori, Z. Hou, Chem. Eur. J. 17, 5033-5044 (2011), (3) F. Guo, M. Nishiura, H. Koshino, Z. Hou, Macromolecules. 44, 6335-6344 (2011), (4) References: Tardif, O.; Nishiura, M.; Hou, ZM Organometallics 22, 1171, (2003); (5) References: Hultzsch, KC; Spaniol, TP; Okuda, J. Angew. Chem. Int. Ed, 38, 227, (1999); (6) References: International Publication No. WO2006 / 004068; (7) References: Japanese Patent Publication No. 2008-222780; and (8) References: Japanese Patent Publication No. 2008-095008.

[0037] The ionic compound, when combined with the metallocene complex, allows the metallocene complex to exhibit activity as a polymerization catalyst. The mechanism of this is thought to be that the ionic compound reacts with the metallocene complex to generate a cationic complex (active species).

[0038] The ionic compound contained in the catalyst composition is not particularly limited, but examples thereof include a combination of non-coordinating anions and cations. Preferred examples include triphenylcarbonium tetrakis(pentafluorophenyl)borate, triphenylcarbonium tetrakis(tetrafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, 1,1'-dimethylferrocenium tetrakis(pentafluorophenyl)borate, etc. One type of ionic compound may be used, or two or more types may be used in combination. Of these, triphenylcarbonium tetrakis(pentafluorophenyl)borate is preferable.

[0039] In the above catalyst composition, the molar ratio of the ionic compound to the metallocene complex varies depending on the types of the complex and the ionic compound, and can be appropriately set. The molar ratio is preferably 0.5 to 1 relative to the central metal of the metallocene complex when the ionic compound is, for example, one consisting of a carbonium cation and a boron anion (e.g., [Ph3C][B(C6F5)4]), and is preferably about 10 to 4000 relative to the central metal of the metallocene complex when the ionic compound is an alkylaluminum compound such as methylaluminoxane. The ionic compound is considered to ionize, i.e., cationize, the metallocene complex to make it a catalytically active species. Within the above-mentioned ratio range, the metallocene complex can be sufficiently activated, and the ionic compound consisting of the carbonium cation and the boron anion does not become excessive, reducing the risk of causing an undesired reaction with the monomer to be polymerized.

[0040] The catalyst composition can be used as a polymerization catalyst composition to polymerize (addition polymerize) ethylene and anisylpropylenes to produce a copolymer. For example, the polymerization catalyst composition can be used by 1) providing a composition containing each component (such as a metallocene complex and an ionic compound) in a polymerization reaction system, or by 2) providing each component separately in a polymerization reaction system and allowing the composition to be constituted in the reaction system. In the above 1), "providing as a composition" includes providing a metallocene complex (active species) that has been activated by a reaction with an ionic compound.

[0041] Specifically, the method for producing the copolymer can be carried out, for example, by the following procedure. 1. Polymerizable monomers are supplied to a system (preferably liquid phase) containing a catalyst composition used in a method for producing a polymer, and polymerized. If the monomer is liquid, it can be supplied by dropping, and if it is gas, it can be supplied through a gas pipe (bubbling, etc. in the case of a liquid phase reaction system). 2. Polymerization is carried out by adding a catalyst composition used in a method for producing a polymer to a system (preferably in a liquid phase) containing a polymerizable monomer, or by adding the components of the catalyst composition separately. The catalyst composition to be added may be prepared in advance (preferably in a liquid phase) and activated (in this case, it is preferable to add the catalyst composition without exposing it to the outside air).

[0042] The production method may be any method such as gas phase polymerization, solution polymerization, suspension polymerization, liquid phase bulk polymerization, emulsion polymerization, solid phase polymerization, etc. In the case of the solution polymerization method, the solvent used is not particularly limited as long as it is inert in the polymerization reaction, can dissolve the monomer and the catalyst, and does not interact with the catalyst. Examples of the solvent include saturated aliphatic hydrocarbons such as butane, pentane, hexane, and heptane; saturated alicyclic hydrocarbons such as cyclopentane and cyclohexane; aromatic hydrocarbons such as benzene and toluene; and halogenated hydrocarbons such as methylene chloride, chlorobenzene, bromobenzene, and chlorotoluene. In addition, a solvent that is not toxic to living organisms is preferable. Specifically, aromatic hydrocarbons, particularly toluene, are preferable. The solvent may be used alone or in combination of two or more. The amount of the solvent used is arbitrary. For example, the concentration of the complex contained in the polymerization catalyst is 1.0×10 -5 ~1.0×10 -1 It is preferable that the amount is in mol / L.

[0043] The amount of monomer to be subjected to the polymerization reaction can be appropriately set depending on the target polymer to be produced. For example, the amount of monomer is preferably 100 times or more, 200 times or more, or 500 times or more in terms of molar ratio to the metallocene complex constituting the polymerization catalyst composition.

[0044] When the polymerization is carried out by solution polymerization, the polymerization temperature can be any temperature, for example, in the range of −90 to 100° C. The temperature can be appropriately selected depending on the type of monomer to be polymerized, and the like, but the polymerization can usually be carried out at about room temperature, that is, about 25° C. The polymerization time is about several seconds to several days and may be appropriately selected depending on the type of monomer to be polymerized, etc. It may be 1 hour or less, or in some cases 1 minute or less. However, these reaction conditions can be appropriately selected depending on the polymerization reaction temperature, the type and molar amount of the monomer, the type and amount of the catalyst composition, etc., and are not limited to the ranges exemplified above.

[0045] In addition, 1) an alternating copolymer can be produced by polymerizing a mixture of two or more types of monomers in the presence of a catalyst composition, and 2) a block copolymer can be produced by supplying each monomer in turn to a reaction system containing a catalyst composition.

[0046] After the polymerization step, any step such as a purification step or a polar group induction step can be carried out.

[0047] The anisylpropylenes used in the above-mentioned method for producing the copolymer include, for example, the compound represented by the following formula (I). [ka] (In the formula, R is a substituent of an aromatic ring, and m is an integer of 0 to 4.)

[0048] R, which is a substituent of an aromatic ring, is not particularly limited, and examples thereof include a halogen atom, a hydrocarbyl group having 1 to 10 carbon atoms, an alkylthio group having 1 to 10 carbon atoms, an alkylamino group having 1 to 10 carbon atoms, and an alkoxy group having 1 to 10 carbon atoms. When R is a hydrocarbyl group, it may be bonded to form a saturated, unsaturated, or hetero-condensed ring. The substitution position of R in an aromatic ring is not limited, but is preferably the m position. m is an integer of 1 to 4, and preferably an integer of 1 to 2. Examples of halogen atoms include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. The hydrocarbyl group having 1 to 10 carbon atoms is preferably a linear or branched alkyl group, alkenyl group, or alkynyl group having 1 to 6 carbon atoms, and more preferably includes a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an n-hexyl group, etc. The alkylthio group having 1 to 10 carbon atoms is preferably an alkylthio group having 1 to 6 carbon atoms, and examples thereof include a methylthio group, an ethylthio group, an n-propylthio group, an isopropylthio group, an n-butylthio group, an isobutylthio group, a sec-butylthio group, a tert-butylthio group, an n-pentylthio group, and an n-hexylthio group. The alkylamino group having 1 to 10 carbon atoms is preferably an alkylamino group having 1 to 6 carbon atoms. The alkylamino group is preferably a dialkylamino group, and the alkyls substituting the amino groups may be the same or different. More preferred examples of the alkylamino group include dialkylamino groups such as dimethylamino group, diethylamino group, di-n-propylamino group, diisopropylamino group, di-n-butylamino group, diisobutylamino group, di-sec-butylamino group, and di-tert-butylamino group. The alkoxy group having 1 to 10 carbon atoms is preferably an alkoxy group having 1 to 3 carbon atoms, and examples thereof include a methoxy group, an ethoxy group, and a propoxy group. Examples of the saturated fused ring formed when R is bonded to another R and fused with the aromatic ring that R substitutes include a naphthalene ring. Examples of the hetero fused ring formed by R bonding to each other and condensing with the aromatic ring substituted by R include an indole ring, an isoindole ring, a quinoline ring, an isoquinoline ring, a carbazole ring, an acridine ring, a benzofuran ring, a benzopyran ring, a benzothiophene ring, etc. The fused ring may have 1 to 6 substituents, and examples of the substituents include the above-mentioned halogen atoms, hydrocarbyl groups having 1 to 10 carbon atoms, alkylthio groups having 1 to 10 carbon atoms, alkylamino groups having 1 to 10 carbon atoms, and alkoxy groups having 1 to 10 carbon atoms.

[0049] Specific preferred examples of the compound represented by the above formula (I) include substituted 2-allylanisoles (hereinafter referred to as "APs") such as 2-allyl-4-fluoroanisole, 2-allyl-4,5-difluoroanisole, 2-allyl-4-methylanisole, 2-allyl-4-tert-butylanisole, 2-allyl-4-hexylanisole, 2-allyl-4-methoxyanisole, and 3-(2-methoxy-1-naphthyl)-1-propylene. R "); unsubstituted 2-allylanisole (3-(2-anisyl)-1-propylene) (hereinafter also referred to as "AP"); and the like.

[0050] The anisylpropylenes used in the polymerization reaction may be used alone or in combination of two or more kinds.

[0051] The anisylpropylenes and ethylene may be synthesized according to a common method in the field of organic chemistry, or may be commercially available.

[0052] The ethylene-anisylpropylene copolymer synthesized by the above-mentioned production method or the like has a molar ratio of the anisylpropylenes of preferably 20 mol% or more, more preferably 30 mol% or more, and may be 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, or 80 mol% or more. The molecular weight distribution of the copolymer is arbitrary, but a copolymer having a relatively narrow molecular weight distribution can be preferably used. Here, the molecular weight distribution may be a value (Mw / Mn) measured by a GPC method (measured at 145°C using polystyrene as a standard substance and 1,2-dichlorobenzene as an eluent), and can be measured using, for example, a GPC measuring device (TOSOH HLC 8321 GPC / HT). The molecular weight distribution of the ethylene-anisilpropylene copolymer is usually expressed as an index, Mw / Mn, of preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.0 or less.

[0053] The number average molecular weight (g / mol) of the ethylene-anisylpropylene copolymer is 3000 or more, preferably 50,000 or more, more preferably 100,000 or more. The number average molecular weight (g / mol) of the ethylene-anisylpropylene copolymer is 700,000 or less, preferably 600,000 or less, more preferably 550,000 or less. Within the above range, the effect tends to be better obtained.

[0054] The mechanism by which a greater effect is obtained when the number average molecular weight of the above ethylene-anisylpropylene copolymer is adjusted to 3,000 or more and 700,000 or less is not clear; however, if the molecular weight is too small, the amount of hard segments is small and sufficient mechanical strength is not obtained, and if the molecular weight is too large, the mobility of the soft segments is reduced and the self-repairing properties are reduced. Therefore, it is presumed that by making the polymer into one with a specified molecular weight, the self-repairing properties are effectively exerted and the crack growth resistance is improved.

[0055] The glass transition point (Tg) of the ethylene-anisylpropylene copolymer may vary depending on the structure of the structural unit derived from the anisylpropylenes. The glass transition point is not particularly limited, but is usually about -40 to 100°C. The glass transition point can be measured by a differential scanning calorimetry (DSC) method or the like. From the viewpoint of self-repairing property, it is desirable that the Tg of the ethylene-anisylpropylene copolymer used as a raw material is room temperature (generally 25°C, but may vary depending on the mode and conditions of use) or lower.

[0056] When the ethylene-anisylpropylene copolymer has a melting point, it varies depending on the structure of the structural unit derived from the anisylpropylenes, the ratio of the structural unit derived from the anisylpropylenes, and other factors, but is usually 100° C. or higher, preferably 110° C. or higher, more preferably 120° C. or higher, and even more preferably 130° C. or higher. The melting point can be measured, for example, by differential scanning calorimetry (DSC).

[0057] The ethylene-anisylpropylene copolymer is a copolymer having a structural unit derived from the anisylpropylene represented by the following formula (A) and a structural unit derived from ethylene represented by the following formula (B).

[0058] Here, R and m in formula (A) are the same as R and m in formula (I) above. [ka]

[0059] The mechanism by which the above-mentioned anisylpropylenes and ethylene copolymers are used is not clear, but it is presumed that the above-mentioned combination causes the alternating copolymerized portions of the anisylpropylenes and ethylene to act as highly mobile soft segments, making it easier to recover from the entanglements of the soft segments and the aggregation of the hard segments, thereby effectively exerting self-repairing properties and improving crack growth resistance.

[0060] The ethylene-anisylpropylene copolymer is a block copolymer consisting of a soft segment block and a hard segment block, the soft segment is composed of an alternating sequence of ethylene and anisylpropylene (anisylpropylenes), the total proportion of the structural units of the soft segments accounts for 60 mol % or more of the total structural units of the copolymer, and the hard segment is composed of polyethylene.

[0061] The ethylene-anisylpropylene copolymer is a block copolymer consisting of a block of a soft segment and a block of a hard segment. The soft segment is an alternating copolymer consisting of ethylene and anisylpropylene (anisylpropylenes) linked together in an alternating manner. The alternating copolymer portion consists of a main sequence in which structural units (A) and (B) are arranged alternately (hereinafter also referred to as an "alternating (A)-(B) sequence" or "(A)-alt-(B) sequence"), but may contain, as a sub-sequence, a sequence in which two or more of each are arranged consecutively to a certain extent. The soft segment is an alternating copolymer, and the proportion of the alternating (A)-(B) sequence in the entire sequence of the ethylene-anisylpropylene copolymer (when the copolymer contains two or more types of anisylpropylene structural units and ethylene structural units, the proportion of the total alternating sequence consisting of anisylpropylene structural units and ethylene structural units) is, in terms of molar ratio, usually 30 mol% or more, preferably 40 mol% or more, more preferably 50 mol% or more, and may be 60 mol% or more, or 70 mol% or more. More specifically, in the embodiment of the alternating polymer, the alternating sequence -(A)-alt-(B)- may be included as well as the polymerization sequence of each of (A) and (B). The proportion of the polymerization sequence -(B)-(B)- of (B) in the entire sequence of the ethylene-anisylpropylene copolymer is usually 60 mol% or less, preferably 50 mol% or less, more preferably 40 mol% or less, and may be 30 mol% or less, or 20 mol% or less, in terms of molar ratio. The proportion of the polymerization sequence -(A)-(A)- of (A) in the entire sequence of the ethylene-anisylpropylene copolymer (when it contains two or more types of anisylpropylene structural units, including random copolymers, alternating copolymers, block copolymers, and other ordered copolymers composed of two or more types of anisylpropylene structural units) is preferably 20 mol% or less, more preferably 10 mol% or less, and may be 5 mol% or less, 3 mol% or less, or 0 mol%.

[0062] The ratio of the sequence is, for example, 1 H-NMR, 13 It can be measured by C-NMR or the like.1 It can be determined by comparing the integral ratios of the peaks at 1.0-1.5 ppm using H-NMR.

[0063] The content of the structural unit of formula (A) and the structural unit of formula (B) contained in the copolymer having the structural units represented by formula (A) and formula (B) is arbitrary. For example, the ratio of the structural unit of formula (A) to the total structural units can be 1 to 99 mol% in terms of molar ratio. In addition, according to the above production method, the ethylene-anisylpropylene copolymer can also be a copolymer having a relatively high ratio of anisylpropylene structural units. Here, the ethylene-anisylpropylene copolymer has a sufficiently high ratio of the structural unit of formula (A), and can have a sufficiently high ratio of alternating (A)-(B) arrangement, which is considered to have an autonomous self-repairing action.The ratio of the anisylpropylene structural unit in the ethylene-anisylpropylene copolymer is usually 20 mol% or more, preferably 30 mol% or more, more preferably 40 mol% or more, and may contain 50 mol% or more, 60 mol% or more, 70 mol% or more, or 80 mol% or more of the structural unit of formula (A) in molar ratio. The ratio of the structural units is, for example, 1 H-NMR, 13 It can be measured by C-NMR or the like. 1 It can be determined by comparing the integral ratio of methylene or methyl hydrogen adjacent to the heteroatom and the hydrocarbon at 1-1.8 ppm by H-NMR. The ratio of the structural unit is controlled by adjusting the ratio of each monomer as the raw material in the production of the ethylene-anisylpropylene copolymer.

[0064] For the soft segment of the ethylene-anisylpropylene copolymer in which ethylene and anisylpropylene are alternately linked, the total ratio of the structural units of the soft segment is 60 mol% or more of the total structural units (100 mol%) of the ethylene-anisylpropylene copolymer. That is, the total ratio of the structural units of the soft segment among all the structural units of the ethylene-anisylpropylene copolymer is 60 mol% or more in molar ratio. The total amount is preferably 61 mol% or more, more preferably 63 mol% or more, and even more preferably 65 mol% or more. The upper limit is preferably 98 mol% or less, more preferably 96 mol% or less, and even more preferably 94 mol% or less. Within the above range, the effect tends to be better obtained.

[0065] In the rubber composition containing the rubber component and the ethylene-anisylpropylene copolymer, the content of the ethylene-anisylpropylene copolymer is preferably 70 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 30 parts by mass or less, based on 100 parts by mass of the rubber component. The lower limit is preferably 2 parts by mass or more, more preferably 7 parts by mass or more, and even more preferably 10 parts by mass or more. Within the above range, the effect tends to be better obtained.

[0066] The rubber composition desirably contains a filler. The filler is not particularly limited, and materials known in the rubber field can be used, for example, inorganic fillers such as carbon black, silica, calcium carbonate, talc, alumina, clay, aluminum hydroxide, aluminum oxide, mica, biochar, poorly dispersible fillers, etc. Among them, carbon black and silica are preferred from the viewpoint of obtaining a greater effect.

[0067] In the rubber composition, the content of the filler (total amount of fillers such as carbon black and silica) is preferably 2 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 50 parts by mass or more, per 100 parts by mass of the rubber component, and is preferably 120 parts by mass or less, more preferably 90 parts by mass or less, even more preferably 80 parts by mass or less, and particularly preferably 70 parts by mass or less. Within the above ranges, the effect tends to be better obtained.

[0068] Carbon black is not particularly limited, but examples thereof include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. Commercially available products include those from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Co., Ltd., Lion Co., Ltd., Shin-Nichika Carbon Co., Ltd., Columbia Carbon Co., Ltd., and the like. These may be used alone or in combination of two or more. In addition to conventional carbon black made from mineral oils and the like, carbon black made from biomass materials such as lignin may also be used. Furthermore, regenerated carbon black (recycled carbon black) may also be used.

[0069] The nitrogen adsorption specific surface area (N2SA) of carbon black is 5m 2 / g or more is preferable, and 50m 2 / g or more is more preferable, and 90m 2 / g or more is more preferable. 2 / g or less is preferable, and 130m 2 / g or less is more preferable, and 120m 2 Within the above range, there is a tendency that the effect is better obtained. The nitrogen adsorption specific surface area of ​​carbon black can be determined in accordance with JIS K6217-2:2001.

[0070] In the rubber composition, the content of carbon black is preferably 2 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 50 parts by mass or more, and is preferably 120 parts by mass or less, more preferably 90 parts by mass or less, even more preferably 80 parts by mass or less, and particularly preferably 70 parts by mass or less, based on 100 parts by mass of the rubber component. When the content is within the above range, the effect tends to be better obtained.

[0071] In the rubber composition, examples of silica that can be used include dry process silica (anhydrous silica) and wet process silica (hydrated silica). Among them, wet process silica is preferred because it has a large number of silanol groups. Commercially available products include those from Degussa, Rhodia, Tosoh Silica, Solvay Japan, and Tokuyama. These may be used alone or in combination of two or more.

[0072] As the silica, plant-derived silica can also be suitably used. Examples of plant-derived silica include silica derived from plants containing silica. Examples of plants containing silica include rice, corn, sugarcane, horsetail, wheat, barley, rye, pearl barley, millet, foxtail millet, Japanese barnyard millet, and Erianthus. In addition, the saccharification residue of the above-mentioned plants containing silica can also be used. Among them, rice husks and straws with high silica content are preferred, and rice husks are more preferred. In addition, the plant containing silica may be one that has been burned to ash or one that has been carbonized.

[0073] When the rubber composition contains silica, the content of silica is preferably 2 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 50 parts by mass or more, and is preferably 120 parts by mass or less, more preferably 90 parts by mass or less, even more preferably 80 parts by mass or less, and particularly preferably 70 parts by mass or less, based on 100 parts by mass of the rubber component. When the content is within the above range, the effect tends to be better obtained.

[0074] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 50 m 2 / g or more, more preferably 100m 2 / g or more, more preferably 150m 2 The upper limit of the N2SA of silica is not particularly limited, but is preferably 350 m 2 / g or less, more preferably 300m 2 / g or less, more preferably 250m 2 Within the above range, there is a tendency for the effect to be better obtained. The N2SA of silica is a value measured by the BET method in accordance with ASTM D3037-93.

[0075] Examples of the poorly dispersible filler include microfibrillated vegetable fibers, short fiber cellulose, gel compounds, etc. Among these, microfibrillated vegetable fibers are preferred.

[0076] The microfibrillated plant fiber is preferably cellulose microfibril, since it has good reinforcing properties. The cellulose microfibril is not particularly limited as long as it is derived from a natural product, and examples thereof include those derived from resource biomass such as fruits, grains, and root vegetables, wood, bamboo, hemp, jute, and kenaf, and pulp, paper, cloth, agricultural waste, waste biomass such as food waste and sewage sludge obtained from these as raw materials, unused biomass such as rice straw, wheat straw, and thinned wood, as well as cellulose produced by sea squirts, acetic acid bacteria, etc. These microfibrillated plant fibers may be used alone or in combination of two or more.

[0077] In this specification, cellulose microfibrils typically refer to cellulose fibers having an average fiber diameter of 10 μm or less, more typically cellulose fibers having a microstructure formed by the aggregation of cellulose molecules and an average fiber diameter of 500 nm or less. Typical cellulose microfibrils are formed, for example, as an aggregate of cellulose fibers having the above-mentioned average fiber diameter.

[0078] When the rubber composition contains a poorly dispersible filler, the content of the poorly dispersible filler is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and particularly preferably 10 parts by mass or less. Within the above range, the effect tends to be better obtained.

[0079] When the rubber composition contains silica, it is preferable that the rubber composition further contains a silane coupling agent. The silane coupling agent is not particularly limited, and those known in the rubber field can be used. For example, bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)disulfide, bis(4-triethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, 3-trimethoxysilylpropyl-N, Examples of such silylsilanes include sulfide-based silylsilanes such as N-dimethylthiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 3-triethoxysilylpropyl methacrylate monosulfide; mercapto-based silylsilanes such as 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and Momentive's NXT and NXT-Z; vinyl-based silylsilanes such as vinyltriethoxysilane and vinyltrimethoxysilane; amino-based silylsilanes such as 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; glycidoxy-based silylsilanes such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silylsilanes such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chloro-based silylsilanes such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. Commercially available products include those manufactured by Degussa, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industry, Azumax, and Dow Corning Toray Co., Ltd. These may be used alone or in combination of two or more.

[0080] In the rubber composition, the content of the silane coupling agent is preferably 0.1 parts by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more, based on 100 parts by mass of silica. The upper limit of the content is preferably 50 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, and particularly preferably 10 parts by mass or less. Within the above range, the effect tends to be better obtained.

[0081] The rubber composition may contain a plasticizer. In this specification, the plasticizer is a material that imparts plasticity to the rubber component, and may be liquid or solid at room temperature (25° C.) These may be used alone or in combination of two or more kinds. In this specification, a copolymer having a structural unit of the above non-polar olefin monomer and a structural unit of the polar olefin monomer represented by the above formula (I) is not included in the plasticizer.

[0082] Examples of the plasticizer include oil, liquid polymer, resin, etc. These may be used alone or in combination of two or more kinds.

[0083] The oil is not particularly limited, and may be any conventionally known oil, such as paraffinic process oil, aromatic process oil, naphthenic process oil, low PCA (polycyclic aromatic) process oil such as TDAE and MES, vegetable-derived oil, and mixtures thereof. These may be used alone or in combination of two or more. From the viewpoint of life cycle analysis, lubricating oil or waste edible oil after use in a rubber mixing mixer or automobile engine may be used as appropriate.

[0084] Examples of the plant-derived oils (also called vegetable oils) include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, rosin, pine oil, pine tar, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive oil, sunflower oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, and tung oil.

[0085] As the above oil, for example, products from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., Japan Energy Co., Ltd., Orisoi Co., Ltd., H&R Co., Ltd., Toyokuni Oil Mills Co., Ltd., Showa Shell Sekiyu K.K., Fuji Kosan Co., Ltd., Nisshin Oillio Group Co., Ltd., etc. can be used.

[0086] Examples of the liquid polymer include liquid diene polymers (liquid rubber) and liquid farnesene polymers at 25°C. Examples of liquid rubber include liquid styrene butadiene copolymers (liquid SBR), liquid butadiene polymers (liquid BR), liquid isoprene polymers (liquid IR), liquid styrene isoprene copolymers (liquid SIR), liquid styrene butadiene styrene block copolymers (liquid SBS block polymers), and liquid styrene isoprene styrene block copolymers (liquid SIS block polymers). The ends or main chains of these may be modified with polar groups. Hydrogenated products of these may also be used.

[0087] The liquid diene polymer has a weight average molecular weight (Mw) of 1.0×10 in terms of polystyrene measured by gel permeation chromatography (GPC). 3 ~5.0×10 4 Preferably, it is 3.0×10 3 ~1.5×10 4 The lower or upper limit of Mw of the liquid diene polymer may be 4,500 or 8,500. In this specification, the Mw of the liquid diene-based polymer is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).

[0088] As the liquid diene polymer, for example, products available from Sartomer Co., Ltd., Kuraray Co., Ltd., etc. can be used.

[0089] The resin may be a resin that is commonly used as a tire compound, and may be liquid or solid at room temperature (25°C). Examples of the resin include aromatic vinyl polymers, coumarone-indene resins, coumarone resins, indene resins, phenolic resins, rosin resins, petroleum resins, terpene resins, and acrylic resins. The resin may also be a hydrogenated resin (hydrogenated resin). These may be used alone or in combination of two or more. The resin itself may also be a copolymer of monomer components of multiple origins. Among these, aromatic vinyl polymers, petroleum resins, terpene resins, and hydrogenated resins thereof are preferable.

[0090] When a resin that is solid at room temperature is used, the softening point of the resin is preferably 50° C. or higher, more preferably 55° C. or higher, even more preferably 60° C. or higher, and particularly preferably 85° C. or higher. Also, the softening point is preferably 160° C. or lower, more preferably 150° C. or lower, even more preferably 140° C. or lower, and particularly preferably 100° C. or lower. Within the above range, the effect tends to be better obtained. When the resin is liquid at room temperature, the softening point is preferably 20° C. or lower, more preferably 10° C. or lower, and even more preferably 0° C. or lower. In the case of hydrogenated resins, it is desirable for the softening point to be similar to that mentioned above. The softening point of the resin is the temperature at which the ball drops when the softening point specified in JIS K6220-1:2001 is measured using a ring and ball softening point tester.

[0091] The aromatic vinyl polymer is a polymer containing an aromatic vinyl monomer as a structural unit. For example, it can be a resin obtained by polymerizing α-methylstyrene and / or styrene, and specifically, it can be a homopolymer of styrene (styrene resin), a homopolymer of α-methylstyrene (α-methylstyrene resin), a copolymer of α-methylstyrene and styrene, a copolymer of styrene and another monomer, etc.

[0092] The coumarone-indene resin is a resin containing coumarone and indene as main monomer components constituting the resin skeleton (main chain). Other monomer components contained in the skeleton besides coumarone and indene include styrene, α-methylstyrene, methylindene, vinyltoluene, etc.

[0093] The coumarone resin is a resin containing coumarone as a main monomer component constituting the skeleton (main chain) of the resin.

[0094] The indene resin is a resin containing indene as a main monomer component constituting the skeleton (main chain) of the resin.

[0095] The phenolic resin may be a known polymer obtained by reacting phenol with an aldehyde such as formaldehyde, acetaldehyde, or furfural in the presence of an acid or alkali catalyst. Among these, those obtained by reacting with an acid catalyst (such as novolac-type phenolic resin) are preferred.

[0096] Examples of the rosin resin include rosin-based resins such as natural rosin, polymerized rosin, modified rosin, ester compounds thereof, and hydrogenated products thereof.

[0097] Examples of the petroleum resin include C5 resin, C9 resin, C5 / C9 resin, dicyclopentadiene (DCPD) resin, C9 / DCPD resin, and hydrogenated versions of these resins. Among these, DCPD resin, hydrogenated DCPD resin, C9 / DCPD resin, and C9 / hydrogenated DCPD resin are preferred.

[0098] The terpene resin is a polymer containing terpene as a constituent unit. For example, polyterpene resin obtained by polymerizing a terpene compound, aromatic modified terpene resin obtained by polymerizing a terpene compound and an aromatic compound, etc. can be mentioned. As the aromatic modified terpene resin, terpene phenol resin made from terpene compounds and phenolic compounds, terpene styrene resin made from terpene compounds and styrene compounds, and terpene phenol styrene resin made from terpene compounds, phenolic compounds, and styrene compounds can also be used. In addition, examples of the terpene compound include α-pinene, β-pinene, etc., examples of the phenolic compound include phenol, bisphenol A, etc., and examples of the aromatic compound include styrene compounds (styrene, α-methylstyrene, etc.). Among them, aromatic modified terpene resin is preferable.

[0099] The acrylic resin is a polymer containing an acrylic monomer as a constituent unit. For example, a styrene-acrylic resin having a carboxyl group and obtained by copolymerizing an aromatic vinyl monomer component and an acrylic monomer component, such as a styrene-acrylic resin, can be used. Among them, a solventless carboxyl group-containing styrene-acrylic resin can be preferably used.

[0100] Examples of the resins that can be used include products from Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Company, Exxon Mobil Corporation, KRATON, Nippon Paint Chemical Co., Ltd., Nippon Shokubai Co., Ltd., ENEOS Corporation, Arakawa Chemical Industries, Ltd., and Taoka Chemical Co., Ltd.

[0101] From the viewpoint of sustainability, it is desirable to use, as the plasticizer, a plant-derived plasticizer such as the plant-derived oil or farnesene-based polymer.

[0102] Farnesene polymers are polymers obtained by polymerizing farnesene and have structural units based on farnesene. Farnesene has isomers such as α-farnesene ((3E,7E)-3,7,11-trimethyl-1,3,6,10-dodecatetraene) and β-farnesene (7,11-dimethyl-3-methylene-1,6,10-dodecatriene), but (E)-β-farnesene, which has the following structure, is preferred. [ka]

[0103] The farnesene-based polymer may be a homopolymer of farnesene (farnesene homopolymer) or a copolymer of farnesene and a vinyl monomer (farnesene-vinyl monomer copolymer). These may be used alone or in combination of two or more. Among them, a copolymer of farnesene and a vinyl monomer is preferred.

[0104] Examples of vinyl monomers include aromatic vinyl compounds such as styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, α-methylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 4-tert-butylstyrene, 5-t-butyl-2-methylstyrene, vinylethylbenzene, divinylbenzene, trivinylbenzene, divinylnaphthalene, tert-butoxystyrene, vinylbenzyldimethylamine, (4-vinylbenzyl)dimethylaminoethylether, N,N-dimethylaminoethylstyrene, N,N-dimethylaminomethylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-t-butylstyrene, 3-t-butylstyrene, 4-t-butylstyrene, vinylxylene, vinylnaphthalene, vinyltoluene, vinylpyridine, diphenylethylene, and tertiary amino group-containing diphenylethylene, as well as conjugated diene compounds such as butadiene and isoprene. These may be used alone or in combination of two or more. Among these, butadiene is preferred. That is, the farnesene-vinyl monomer copolymer is preferably a copolymer of farnesene and butadiene (farnesene-butadiene copolymer).

[0105] In the farnesene-vinyl monomer copolymer, the copolymerization ratio by mass of farnesene and vinyl monomer (farnesene / vinyl monomer) is preferably 40 / 60 to 90 / 10.

[0106] The farnesene-based polymer preferably has a weight average molecular weight (Mw) of 3000 or more and 300,000 or less. The Mw of the farnesene-based polymer is preferably 8000 or more, more preferably 10,000 or more, and is preferably 100,000 or less, more preferably 60,000 or less, and even more preferably 50,000 or less. Within the above ranges, the effect tends to be more preferably obtained.

[0107] The farnesene-based polymer may be either a liquid or solid polymer at room temperature (25° C.), and is preferably a liquid farnesene-based polymer that is a liquid at room temperature (25° C.).

[0108] When the rubber composition contains a plasticizer, the content of the plasticizer (total amount of the plasticizer) is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less. Within the above range, the effect tends to be better obtained. The plasticizer content includes the amount of oil and resin contained in the oil-extended rubber and resin-extended rubber.

[0109] In the rubber composition, the content of the solid plasticizer in a solid state at room temperature (25°C) is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 7 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 12 parts by mass or less. Within the above range, the effect tends to be better obtained. The content of the resin in a solid state at room temperature (25° C.) is also desirably in the same range.

[0110] In the rubber composition, the content of the liquid plasticizer in a liquid state at room temperature (25°C) is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less. Within the above range, the effect tends to be better obtained. The liquid plasticizer content includes the amount of oil contained in the oil-extended rubber and the amount of liquid resin in the resin-extended rubber that has been extended with the liquid resin. A similar range is also desirable for the oil content that is liquid at room temperature (25°C).

[0111] From the viewpoints of crack resistance, ozone resistance, and the like, the rubber composition preferably contains an antioxidant.

[0112] The antiaging agent is not particularly limited, and examples thereof include naphthylamine-based antiaging agents such as phenyl-α-naphthylamine; diphenylamine-based antiaging agents such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, Examples of the antioxidant include p-phenylenediamine antioxidants such as amines; quinoline antioxidants such as polymerized 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. Among these, p-phenylenediamine antioxidants and quinoline antioxidants are preferred, and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and polymerized 2,2,4-trimethyl-1,2-dihydroquinoline are more preferred. Commercially available products include, for example, products from Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., and Flexis Co., Ltd.

[0113] In the rubber composition, the content of the antioxidant is preferably 0.2 parts by mass or more, more preferably 2.0 parts by mass or more, and even more preferably 3.4 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 10.0 parts by mass or less, and more preferably 6.0 parts by mass or less.

[0114] The rubber composition preferably contains stearic acid. In the above rubber composition, the content of stearic acid is preferably 0.5 parts by mass or more, more preferably 1.5 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the rubber component.

[0115] As the stearic acid, any conventionally known product can be used, for example, products available from NOF Corp., Kao Corp., Fujifilm Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., and the like.

[0116] The rubber composition preferably contains zinc oxide. In the above rubber composition, the content of zinc oxide is preferably 0.5 parts by mass or more, more preferably 1.5 parts by mass or more, and preferably 6.0 parts by mass or less, more preferably 4.0 parts by mass or less, based on 100 parts by mass of the rubber component.

[0117] As the zinc oxide, any known zinc oxide can be used, for example, products available from Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., etc.

[0118] The rubber composition may contain wax. In the rubber composition, the wax content is preferably 0.5 parts by mass or more, more preferably 1.6 parts by mass or more, and preferably 8.0 parts by mass or less, more preferably 5.0 parts by mass or less, based on 100 parts by mass of the rubber component.

[0119] The wax is not particularly limited, and examples thereof include petroleum waxes, natural waxes, etc. Also, synthetic waxes obtained by refining or chemically treating multiple waxes can be used. These waxes may be used alone or in combination of two or more kinds.

[0120] Examples of petroleum waxes include paraffin wax and microcrystalline wax. Examples of natural waxes are not particularly limited as long as they are derived from resources other than petroleum, and include, for example, vegetable waxes such as candelilla wax, carnauba wax, Japan wax, rice wax, and jojoba wax; animal waxes such as beeswax, lanolin, and spermaceti; mineral waxes such as ozokerite, ceresin, and petrolactam; and refined products thereof. Examples of commercially available products include products from Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., and Seiko Chemical Co., Ltd.

[0121] It is preferable to compound sulfur into the rubber composition in order to form an appropriate amount of crosslinked chains in the polymer chains and impart good performance.

[0122] In the rubber composition, the amount of sulfur is preferably 1.0 part by mass or more, more preferably 1.3 parts by mass or more, and even more preferably 1.6 parts by mass or more, based on 100 parts by mass of the rubber component. The amount is preferably 7.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 4.0 parts by mass or less.

[0123] Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are commonly used in the rubber industry. Commercially available products include those from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Corporation, Nippon Kanzuri Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. These may be used alone or in combination of two or more kinds.

[0124] The rubber composition preferably contains a vulcanization accelerator. In the rubber composition, the content of the vulcanization accelerator is not particularly limited and may be freely determined according to the desired vulcanization speed and crosslink density, but is preferably 0.1 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.7 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 8.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 4.0 parts by mass or less.

[0125] The type of vulcanization accelerator is not particularly limited, and commonly used ones can be used. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and N-cyclohexyl-2-benzothiazyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, Nt-butyl-2-benzothiazolyl sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-orthotolyl guanidine, and orthotolyl biguanidine. These may be used alone or in combination of two or more. Among them, sulfenamide-based, guanidine-based and benzothiazole-based vulcanization accelerators are preferred.

[0126] In addition to the above-mentioned components, the rubber composition may contain compounding agents generally used in the tire industry, such as materials such as a mold release agent.

[0127] The rubber composition containing the rubber component and the ethylene-anisylpropylene copolymer satisfies the following formula (1). The content [mass%] of the rubber component in the rubber composition / the content [mass%] of the ethylene-anisylpropylene copolymer in the rubber composition>1.0 (1) The right side of formula (1) is preferably 2.0, more preferably 3.0, and even more preferably 3.2. The upper limit of the content [mass%] of the rubber in the rubber composition / the content [mass%] of the ethylene-anisylpropylene copolymer in the rubber composition is preferably 10.0 or less, more preferably 7.0 or less, and even more preferably 5.0 or less. Within the above range, the effect tends to be better obtained. In this specification, "the content [mass %] of the rubber component in the rubber composition" refers to the content [mass %] of the rubber component in 100 mass % of the rubber composition. "The content [mass %] of the ethylene-anisylpropylene copolymer in the rubber composition" refers to the content [mass %] of the ethylene-anisylpropylene copolymer in 100 mass % of the rubber composition.

[0128] From the viewpoint of obtaining a greater effect, it is desirable that the rubber composition contains the filler and satisfies the following formula (4). The content of the rubber component in the rubber composition [mass%] / The content of the filler in the rubber composition [mass%] > 1.0 (4) The right side of formula (4) is preferably 1.1, more preferably 1.2, and even more preferably 1.3. The upper limit of the content [mass%] of the rubber component in the rubber composition / the content [mass%] of the filler in the rubber composition is preferably 3.0 or less, more preferably 2.0 or less, and even more preferably 1.5 or less. Within the above range, the effect tends to be better obtained. In this specification, "the content [mass %] of the filler in the rubber composition" refers to the content [mass %] of the filler in 100 mass % of the rubber composition.

[0129] The mechanism by which greater effectiveness is achieved when formula (4) is satisfied is not clear, but it is presumed that when the amount of filler is small, the filler that inhibits self-repairing properties is less likely to fill the non-polar olefin-polar olefin copolymer phase, which is the island phase, and the self-repairing properties are effectively exerted, thereby improving crack growth resistance.

[0130] The rubber composition can be produced, for example, by kneading the above-mentioned components using a rubber kneading device such as an open roll or a Banbury mixer, and then vulcanizing the mixture.

[0131] As for the kneading conditions, in the base kneading step in which additives other than the crosslinking agent (vulcanizing agent) and the vulcanization accelerator are kneaded, the kneading temperature is preferably 100°C or higher, more preferably 120°C or higher, and also preferably 180°C or lower, more preferably 170°C. In the finish kneading step in which the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is preferably 80°C or higher, and also preferably 120°C or lower, more preferably 110°C or lower. In addition, the composition kneaded with the vulcanizing agent and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. The vulcanization temperature is preferably 140°C or higher, more preferably 150°C or higher, and also preferably 190°C or lower, more preferably 185°C or lower.

[0132] In the rubber composition, the average domain diameter of the ethylene-anisylpropylene copolymer in the rubber composition is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more, and is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 1 μm or less. When it is within the above range, the effect tends to be better obtained.

[0133] The average domain diameter of the non-polar olefin-polar olefin copolymer in the rubber composition can be measured by staining with an appropriate staining agent such as osmium tetroxide, followed by measurement using a scanning electron microscope.

[0134] The mechanism by which a greater effect is obtained when the average domain diameter of the above copolymer is adjusted to a specified range is not clear, but if the domain system is too small, sufficient force is not applied to the domain, and if the domain system is too large, there is a risk that the domain will act as a foreign body and reduce the mechanical properties. It is presumed that when the average domain diameter is within the specified range, there is no risk of either of these, and the self-repairing property is effectively exhibited, thereby improving the crack growth resistance.

[0135] Although the method for adjusting the domain diameter of the copolymer in the rubber composition is not clear, it is presumed that it can be controlled by, for example, the kneading time or kneading temperature.

[0136] The rubber composition is used for tire components. As tire components, the rubber composition can be applied (as a rubber composition for tires) to tire components such as, for example, treads (cap treads, base treads, etc.), sidewalls, clinches, bead apexes, breaker cushion rubbers, carcass cord covering rubbers, insulations, chafers, inner liners, etc., and side reinforcing layers of run-flat tires. Among these, from the viewpoint of obtaining a greater effect, the tire components are preferably the tread and the sidewall.

[0137] The tire member made of the rubber composition has an autonomous self-repairing action and is excellent in crack growth resistance. The mechanism of the autonomous self-repairing action and excellent crack growth resistance is considered to be that the structural units of ethylene and the structural units of the anisylpropylenes have an alternating arrangement, and the anisylpropylenes units are regularly distributed as side chains in the skeleton of the alternating copolymer. This may have enhanced molecular entanglement between damaged surfaces and between polymer chains without serious effects from water, acid, or base. In addition, self-repair (i.e., autonomous self-repair) is possible not only in air but also in water, acid, and alkaline solutions without the need for external energy or stimuli (pressure, temperature, etc.). Although external energy or stimuli (pressure, temperature, etc.) are not particularly required for the self-repairing action, it is possible to add them. The addition of external energy or stimuli (pressure, temperature, etc.) is considered to have the advantage of improving the self-repair speed.

[0138] Here, "self-repair" refers to the process in which, when damage such as scratches or cut surfaces of a rubber composition are brought into contact with each other, entanglement of copolymer chains occurs again, and the rubber composition returns to its shape, physical properties, etc. before the damage. The self-repairing action can be confirmed, for example, by contacting the damaged area, leaving it at a predetermined temperature in a predetermined environment for a predetermined time, and comparing the shape, physical properties, etc. after the damage with those before the damage. Specifically, the self-repairing action can be confirmed, for example, by the method described in the Examples below.

[0139] The tire of the present invention is manufactured by a conventional method using the above rubber composition. That is, the composition, which contains various additives as necessary, is extruded in an unvulcanized state to match the shapes of various tire components such as a cap tread, molded in a tire building machine by a conventional method, laminated together with other tire components to form an unvulcanized tire, and then heated and pressurized in a vulcanizer to manufacture the tire.

[0140] The tire is not particularly limited, and examples thereof include pneumatic tires, solid tires, airless tires, etc. Among these, pneumatic tires are preferred.

[0141] The above tires are suitably used as passenger car tires, large passenger car tires, large SUV tires, truck and bus tires, motorcycle tires, racing tires, winter tires (studless tires, snow tires, studded tires), all-season tires, run-flat tires, aircraft tires, mining tires, etc.

[0142] The tire includes a tire member made of the rubber composition. In the tire, the maximum thickness of the tire member is preferably 0.2 mm or more, more preferably 1.0 mm or more, and even more preferably 2.0 mm or more. The upper limit of the maximum thickness of the tire member is preferably 14.0 mm or less, more preferably 12.0 mm or less, even more preferably 10 mm or less, and particularly preferably 8.0 mm or less. Within the above range, the effect tends to be preferably obtained.

[0143] Although the mechanism by which a greater effect is obtained when the maximum thickness of the tire components is adjusted to a predetermined value or more is not clear, it is believed that by making the thickness greater than the predetermined value, the self-repair function is effectively exerted, making it difficult to suppress crack growth during driving. Therefore, it is presumed that good self-repair properties are imparted and crack growth resistance is improved.

[0144] In this specification, the maximum thickness of a tire component means the maximum thickness of each tire component (tread, etc.). The thickness at each point on the surface of each tire component is the linear distance measured along the normal to the surface of each tire component at that point, and the maximum thickness of each tire component is the maximum thickness at that point.

[0145] In the above tire, the maximum thickness (mm) of the tread is preferably 1.0 mm or more, more preferably 2.0 mm or more, and even more preferably 4.0 mm or more. The upper limit of the maximum thickness of the tread is preferably 14.0 mm or less, more preferably 12.0 mm or less, even more preferably 10.0 mm or less, and particularly preferably 8.0 mm or less. Within the above range, the effect tends to be preferably obtained.

[0146] In this specification, the tread (tread portion) is, for example, composed of the single-layer tread itself (first rubber layer) in the case of a single-layer tread; in the case of a two-layer tread consisting of a cap tread (first rubber layer) as the outermost layer and a base tread (second rubber layer) adjacent to the radially inner side of the cap tread, it is composed of two rubber layers, the cap tread and the base tread; and in the case of a three-layer or more layer tread, it is composed of the cap tread (first rubber layer) as the outermost layer, a second rubber layer adjacent to the radially inner side of the cap tread, and another rubber layer arranged on the radially inner side of the second rubber layer. The maximum tread thickness means the maximum value of the tread thickness. The thickness at each point on the tread surface is the linear distance measured along the normal to the tread surface at that point, and the maximum tread thickness is the maximum value of the thickness at each point. Here, when the tread is made of the rubber composition, it is sufficient that at least a part of the tread (such as a cap tread) is made of the rubber composition.

[0147] In the tire, the tire component is a tread, and the groove depth (mm) of the circumferential groove formed in the tread is preferably 2.0 mm or more, more preferably 4.0 mm or more, even more preferably 5.0 mm or more, and is preferably 20.0 mm or less, more preferably 14.0 mm or less, even more preferably 12.0 mm or less, and particularly preferably 10.0 mm or less. Within the above ranges, the effect tends to be better obtained.

[0148] Although the mechanism by which the effect of adjusting the groove depth of the circumferential grooves formed in the tread to a predetermined range is not clear, it is believed that adjusting the groove depth effectively exerts the self-repair function, making it difficult to suppress crack growth during driving. Therefore, it is presumed that good self-repair properties are imparted and crack growth resistance is improved.

[0149] In this specification, the groove depth of a circumferential groove means the distance measured along the normal to the extension of the surface forming the ground contact surface of the outermost tread surface, from the extension of the surface forming the ground contact surface to the deepest groove bottom, and refers to the maximum distance among the groove depths of the circumferential grooves provided.

[0150] It is desirable that the content [mass%] of the ethylene-anisylpropylene copolymer in the rubber composition constituting the tire member and the maximum thickness [mm] of the tire member in the tire satisfy the following formula (6). The content of the ethylene-anisylpropylene copolymer in the rubber composition [mass %] / maximum thickness of the tire component [mm]<15 (6) The right side of formula (6) is preferably 10, more preferably 7, and even more preferably 5. The lower limit of the content [mass%] of the copolymer in the rubber composition / maximum thickness [mm] of the tire component is preferably 0.4 or more, more preferably 1.0 or more, and even more preferably 2.0 or more. Within the above range, the effect tends to be better obtained.

[0151] Although the mechanism by which the effect is greater when formula (6) is satisfied is unclear, it is believed that by suppressing the content of the polar olefin copolymer relative to the thickness of the tire component, the island phase of the copolymer is effectively formed, and as a result, the self-repairing function is effectively exhibited, making it difficult to suppress crack growth during running. Therefore, it is presumed that good self-repairing properties are imparted and crack growth resistance is improved.

[0152] It is desirable that the content [mass %] of the ethylene-anisylpropylene copolymer in the rubber composition constituting the tire components and the groove depth [mm] of the circumferential groove formed in the tread of the tire satisfy the following formula (9). The content of the ethylene-anisylpropylene copolymer in the rubber composition [mass %] / the groove depth of the circumferential groove formed in the tread [mm] < 10 (9) The right side of formula (9) is preferably 7, more preferably 5, and even more preferably 3. The lower limit of the content [mass%] of the ethylene-anisylpropylene copolymer in the rubber composition / groove depth [mm] of the circumferential groove formed in the tread is preferably 0.4 or more, more preferably 1 or more, and even more preferably 2 or more. Within the above range, the effect tends to be better obtained.

[0153] Although the mechanism by which the effect is improved when formula (9) is satisfied is unclear, it is believed that by suppressing the content of the polar olefin copolymer relative to the groove depth, the island phase of the copolymer is effectively formed, and as a result, the self-repair function is effectively exhibited, making it difficult to suppress the growth of cracks during running. Therefore, it is presumed that good self-repair properties are imparted and the resistance to crack growth is improved.

[0154] In this specification, dimensions such as thickness are measured with the bead portion of the tire aligned to the standard rim width. During measurement, the tire is cut out in the tire radial direction, and both bead ends of the sample are fixed in a state where they are aligned to the standard rim width.

[0155] In this specification, unless otherwise specified, the dimensions of each part of the tire are values ​​measured under normal conditions. In this specification, the term "normal condition" refers to a condition in which the tire is mounted on a normal rim (not shown), inflated to normal internal pressure, and no load is applied.

[0156] When it is not possible to measure with the tire mounted on a regular rim, the dimensions and angles of each part in the meridian section of the tire are measured by cutting the tire along a plane including the axis of rotation, and the distance between the left and right beads in the cross section is measured so that it corresponds to the distance between the beads of the tire mounted on a regular rim.

[0157] "Genuine rim" refers to the rim that is specified for each tire by the standard system that includes the standard on which the tire is based, for example, "Standard rim" in the applicable size listed in the "JATMA YEAR BOOK" for JATMA (Japan Automobile Tire Manufacturers Association), "Measuring Rim" in the "STANDARDS MANUAL" for ETRTO (The European Tire and Rim Technical Organisation), and "Design Rim" in the "YEAR BOOK" for TRA (The Tire and Rim Association, Inc.). Refer to JATMA, ETRTO, and TRA in that order, and follow the standard if there is an applicable size at the time of reference. In the case of a tire not specified in the standard, it refers to the rim that can be assembled to the rim and can hold internal pressure, that is, the rim with the smallest rim diameter and the next narrowest rim width among the rims that do not leak air from between the rim and tire.

[0158] "Regular internal pressure" refers to the air pressure specified for each tire by each standard in the standard system including the standard on which the tire is based. For JATMA, it refers to the "Maximum Air Pressure", for ETRTO, it refers to the "INFLATION PRESSURE", and for TRA, it refers to the maximum value listed in the table "TIRE LOAD LIMITS AT VARIOUS COLD INFLATION PRESSURES". As with "regular rims", it refers to JATMA, ETRTO, TRA in that order and follows those standards. For tires not specified in the standard, it refers to the regular internal pressure (250kPa or more) of another tire size (specified in the standard) that is specified with the regular rim as the standard rim. Note that if multiple regular internal pressures of 250kPa or more are specified, it refers to the smallest value among them.

[0159] In this specification, the term "normal load" refers to the load that is determined for each tire by each standard in the standard system including the standard on which the tire is based, and is the maximum load capacity in the case of JATMA, the "LOAD CAPACITY" in the case of ETRTO, and the maximum value listed in the table "TIRE LOAD LIMITS AT VARIOUS COLD INFLATION PRESSURES" in the case of TRA. As in the case of the "normal rim" and "normal internal pressure" mentioned above, JATMA, ETRTO, and TRA are referred to in that order and their standards are followed. In the case of a tire not determined by a standard, the normal load W is calculated as follows: L Request. V = {(Dt / 2) 2 -(Dt / 2-Ht) 2}×π×Wt W L =0.000011×V+175 W L :Normal load (kg) V: Virtual volume of the tire (mm 3 ) Dt: Tire outer diameter (mm) Ht: Section height of the tire (mm) Wt: tire section width (mm)

[0160] The "section width Wt (mm)" of a tire is the maximum width between the outer surfaces of the sidewalls when the tire is in its normal condition, excluding any patterns or lettering on the sidewalls.

[0161] The "outer diameter Dt (mm)" of a tire refers to the outer diameter of the tire under normal conditions.

[0162] The "section height Ht (mm)" of a tire refers to the radial height of the tire at its radial cross section, and corresponds to half the difference between the tire's outer diameter Dt and the rim diameter R, where R is the tire's rim diameter (mm). In other words, the section height Ht can be calculated by (Dt-R) / 2.

[0163] An example of a tire according to the present invention will be described below with reference to the drawings, but the present invention is not limited to this embodiment.

[0164] 1, the up-down direction is the radial direction of the tire 2, the left-right direction is the axial direction of the tire 2, and the direction perpendicular to the paper surface is the circumferential direction of the tire 2. The tire 2 is symmetrical. The tread 4 has a single-layer structure.

[0165] Although FIG. 1 shows an example of a single-layer structure tread 4, a two-layer structure tread consisting of a cap tread and a base tread, or a tread having a structure of three or more layers may also be used.

[0166] 1, the tread 4 is made of the above rubber composition. The tread 4 contains the above rubber component and the above ethylene-anisylpropylene copolymer, and satisfies the above relational formula (1).

[0167] In the tire 2, each sidewall 6 extends substantially radially inward from an end of the tread 4. A radially outer portion of each sidewall 6 is joined to the tread 4. A radially inner portion of each sidewall 6 is joined to a clinch 10. Each sidewall 6 can prevent damage to the carcass 14.

[0168] 1 is located between the tread 4 and the sidewall 6. The wing 8 is joined to the tread 4 and the sidewall 6, respectively.

[0169] Each clinch 10 is located approximately radially inward of the sidewall 6 and has at least one or more portions that come into contact with the rim.

[0170] The carcass 14 includes a carcass ply 36. In the tire 2, the carcass 14 is made up of one carcass ply 36, but may be made up of two or more carcass plies.

[0171] In the tire 2, the carcass ply 36 is laid between the bead cores 32 on both sides and extends along the tread 4 and the sidewall 6. The carcass ply 36 is folded back from the inside to the outside in the axial direction around each bead core 32. By this folding back, the carcass ply 36 is formed with a main portion 36a and a pair of folded back portions 36b. That is, the carcass ply 36 includes the main portion 36a and a pair of folded back portions 36b.

[0172] Each bead core 32 includes a bead apex 34 extending radially outward from the bead core 32. The bead core 32 is preferably ring-shaped and includes a wound non-stretchable wire. The bead apex 34 tapers radially outward.

[0173] Although not shown, the carcass ply 36 is preferably made of a number of parallel cords and a topping rubber. The absolute value of the angle that each cord makes with respect to the equatorial plane CL is preferably 75° to 90°. In other words, the carcass 14 preferably has a radial structure.

[0174] The belt layer 16 in FIG. 1 is located radially inward of the tread 4. The belt layer 16 is laminated with the carcass 14. The belt layer 16 reinforces the carcass 14. In the tire 2 in FIG. 1, the belt layer 16 is composed of an inner layer 38 and an outer layer 40. As is clear from FIG. 1, it is desirable that the width of the inner layer 38 is slightly larger than the width of the outer layer 40 in the axial direction. In this tire 2, the axial width of the belt layer 16 is preferably 0.6 times or more and 0.9 times or less of the cross-sectional width of the tire 2.

[0175] Each of the inner layer 38 and the outer layer 40 is preferably made of a number of parallel single-wire steel cords (steel monofilaments) and a topping rubber (coating rubber). In other words, the belt layer 16 includes a number of parallel steel monofilaments.

[0176] The band 18 in Fig. 1 is located radially outside the belt layer 16. In the axial direction, the band 18 has a width equal to the width of the belt layer 16. The band 18 may also have a width greater than the width of the belt layer 16.

[0177] Although not shown, the band 18 is preferably made of a cord and a topping rubber. The cord is wound in a spiral shape. This band 18 has a so-called jointless structure. The cord extends substantially in the circumferential direction. The angle of the cord with respect to the circumferential direction is preferably 5° or less, and more preferably 2° or less. Since the belt layer 16 is restrained by the cord, lifting of the belt layer 16 is suppressed.

[0178] 1 constitute a reinforcing layer. The reinforcing layer may be constituted by the belt layer 16 alone.

[0179] FIG. 2 is an enlarged view of the vicinity of the tread 4 in FIG. The tire in FIG. 2 is a tire 2 having a groove 26 on the tire equatorial plane (CL).

[0180] In Fig. 2, the symbol P denotes a point on the tread surface 24. The point P is located outside the groove 26 located most axially inward. The double-headed arrow T denotes the thickness of the tread 4 at the point P. This thickness T is measured along a normal line of the tread surface 24 at the point P. The maximum thickness of the tread 4 is the maximum dimension among the thicknesses of the tread 4 at each point on the tread surface 24.

[0181] The inner liner 20 is located inside the carcass 14. The inner liner 20 is bonded to the inner surface of the carcass 14. A typical base rubber of the inner liner 20 is butyl rubber or halogenated butyl rubber. The inner liner 20 holds the internal pressure of the tire 2.

[0182] Each chafer 22 is located adjacent to a bead 12. In this embodiment, the chafer 22 is preferably made of fabric with rubber impregnated into the fabric. The chafer 22 may be integral with the clinch 10.

[0183] In the tire 2, the tread 4 has a main groove 42 as the groove 26. As shown in FIG. 1, a plurality of main grooves 42, specifically three main grooves 42, are formed in the tread 4. These main grooves 42 are arranged at intervals in the axial direction. The three main grooves 42 are formed in the tread 4, thereby forming four ribs 44 extending in the circumferential direction. In other words, the spaces between the ribs 44 constitute the main grooves 42.

[0184] Each of the main grooves 42 extends in the circumferential direction. The main grooves 42 are continuous in the circumferential direction without interruption. The main grooves 42 facilitate the drainage of water present between the road surface and the tire 2, for example, in rainy weather. Therefore, even if the road surface is wet, the tire 2 can make sufficient contact with the road surface. 2D shows the groove depth of the main groove 42 formed in the tread 4 in the circumferential direction.

[0185] In the tire 2, it is desirable that the tread 4 satisfies the above formulas (2) to (5), and the average domain diameter of the ethylene-anisylpropylene copolymer in the tread 4 is within the above range. In the tire 2 having the tread 4, it is desirable that the maximum thickness of the tread 4 and the groove depth D of the circumferential grooves formed in the tread 4 are within the above range. In the tire 2 having the tread 4, it is desirable that the rubber composition constituting the tread 4, the maximum thickness T of the tread 4, and the groove depth D of the circumferential grooves formed in the tread 4 satisfy the above formulas (6) to (11). EXAMPLES

[0186] In the following, examples (embodiments) that are considered to be preferable for carrying out the present invention will be shown, but the scope of the present invention is not limited to the examples.

[0187] [Polymer synthesis] <Metallocene complex> The metallocene complexes used in the examples were synthesized according to the methods described in the following documents. (1)X.Li, M.Nishiura, K.Mori, T.Mashiko, Z.Hou, Chem.Commun.4137-4139(2007) (2) F. Guo, M. Nishiura, H. Koshino, Z. Hou, Macromolecules.44, 6335-6344 (2011).

[0188] The metallocene complexes used in the examples are as follows: Complex: (C5Me4SiMe3)Sc(CH2C6H4NMe2-o)2 The structure of the metallocene complex used in the examples is shown in FIG.

[0189] <Ionic compounds> [Ph3C][B(C6F5)4] (97%) was purchased from Strem Chemical Corporation and used without purification.

[0190] <Monomer> All monomers were purified prior to use by distillation from Al(octyl)3 (25 wt.% in hexane) and Na. The structures of the anisylpropylenes used in the examples are shown in Figure 4.

[0191] <Measurement method (polymer properties)> (NMR) NMR data of the polymers was obtained using a Bruker AVANCE III HD 500 NMR (FT, 500MHz: 1 H;125MHz: 13 C) Measurements were performed using a spectrometer with CDCl3 (26.8°C) or 1,1,2,2-C2D2Cl4 (120°C) as the solvent. 1 H NMR measurements were performed using tetramethylsilane (TMS) as an internal standard, and the chemical shifts of various solvents are as follows (7.26 ppm: CDCl3, 7.16 ppm: C6D6, 5.32 ppm: CD2Cl2, 6.0 ppm: 1,1,2,2-C2D2Cl4). 13 C NMR chemical shifts are reported relative to the various solvent peaks: CDCl3 (77.16 ppm), CD2Cl2 (53.84 ppm), 1,1,2,2-C2D2Cl4 (73.78 ppm) or C6D6 (128.06 ppm). Coupling constants (J) are given in Hz and indicate overlap of separated peaks. The abbreviations s, d, t, q and m denote singlet, doublet, triplet, quadruplet and multiplet in the respective orders.

[0192] (Gel permeation chromatography (GPC) measurement) The molecular weight and molecular weight distribution of the copolymers were determined by high temperature gel permeation chromatography (HT-GPC) at 145 °C on an HLC-8321 GPC / HT instrument (Tosoh Corporation). 1,2-Dichlorobenzene (DCB) was used as the elution solvent at a flow rate of 1.0 mL / min. Calibration was performed using polystyrene standards (Tosoh Corporation).

[0193] (Differential Scanning Calorimetry (DSC)) DSC measurements were performed on a DSC 7000X (HITACHI) at a rate of 10 °C / min (unless otherwise stated). Thermal history errors in polymers were eliminated by first heating the sample to 150 °C, cooling it at 10 °C / min to -100 °C, and recording a second DSC scan (unless otherwise stated).

[0194] [Production Example 1: Copolymerization of 2-allylanisole (AP) and ethylene (E) (Table 1, Run 1)] In a glove box, a toluene solution (40 mL) of [Ph3C][B(C6F5)4] (323 mg, 0.35 mmol) was slowly added to a toluene solution (10 mL) of (C5Me4SiMe3)Sc(CH2C6H4NMe2-o)2 (complex 1, 177 mg, 0.35 mmol) in a 500 mL autoclave under magnetic stirring. AP (36.3 g, 245 mmol in 350 mL toluene) was then charged. The autoclave was removed from the outside, placed in a water bath (25 °C), and a stainless steel tube was connected. Ethylene was introduced into the system at 1 MPa under magnetic stirring. After 40 min, the polymerization reaction was stopped by adding methanol (4 L). The polymer was collected by filtration, washed with methanol, and dried at 60 °C under reduced pressure for 24 h to obtain a colorless rubbery material (43 g). The physical properties of the obtained polymer P1 were measured and the results are shown in Table 1.

[0195] 13 C{ 1 H} NMR analysis showed that copolymer (P1) mainly had alternating AP-E sequences (61%), with some AP-(E)n-AP sequences (n≧2, 37%) and E-AP-AP-E sequences (2%). In the formulas below, each copolymer is shown diagrammatically with only the alternating AP-E sequence, which is the main sequence. Copolymer (P1) was also amorphous and had a glass transition temperature.

[0196] The measurement results of the physical properties of the obtained polymer (P1) are shown in Table 1 and FIGS. In Table 1, M represents the central metal in the metallocene complex.

[0197] [Table 1]

[0198] The polymer (P1) was a block copolymer consisting of a soft segment block and a hard segment block, and the soft segment was composed of ethylene and 2-allylanisole (AP) linked alternately. In addition, in the polymer (P1), the total proportion of the structural units of the soft segments accounted for 61 mol % of the total structural units of the polymer. The polymer (P1) had a hard segment made of polyethylene and had a number average molecular weight of 210,000 as shown in Table 1.

[0199] Various chemicals used in the production of the rubber compositions (rubber samples) are collectively described below. Note that the chemicals were purified according to standard methods as necessary. SBR: SBR1502 (manufactured by JSR, E-SBR, styrene content: 24% by mass, vinyl content: 17% by mass) Ethylene-anisylpropylene copolymer 1: Polymer (P1) prepared in the above Production Example Carbon black: Show Black N220 (N2SA:111m) manufactured by Cabot Japan Co., Ltd. 2 / g, DBP absorption: 115ml / 100g) Wax: Ozoace 0355 (manufactured by Nippon Seiro Co., Ltd.) Antioxidant 6C: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Antioxidant RD: Nocrac 224 (2,2,4-trimethyl-1,2-dihydroquinoline polymer) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Stearic acid: NOF Corporation Zinc oxide: Three types of zinc oxide (manufactured by Hakusui Tech Co., Ltd.) Oil: H&R VIVATEC 500 (aromatic process oil) Sulfur: Powdered sulfur (Tsurumi Chemical Co., Ltd.) Vulcanization accelerator CZ: Noccela CZ-G (N-cyclohexyl-2-benzothiazolyl sulfenamide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0200] <Production of Rubber Composition (Rubber Sample)> According to the formulations shown in each table, materials other than sulfur and the vulcanization accelerator were kneaded for 5 minutes at 150° C. using a 1.7 L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Sulfur and a vulcanization accelerator were added to the kneaded mixture, and the mixture was kneaded for 5 minutes at 80° C. using an open roll to obtain an unvulcanized rubber composition. The unvulcanized rubber composition was vulcanized at 170° C. for 10 minutes to obtain a rubber composition (rubber sample).

[0201] The rubber compositions (rubber samples) whose formulations were changed according to Table 2 were evaluated by the following evaluation methods. The results are shown in Table 2. The reference comparative example is Comparative Example 1.

[0202] <Crack growth resistance> A flex crack growth test was conducted in accordance with JIS K6260:2017, and the rubber composition (sheet) was bent by repeating 70% elongation 1 million times, and the length of the crack that occurred was measured. The reciprocal of the measured value of the reference comparative example was expressed as an index, with 100. The larger the index, the smaller the crack and the better the crack growth resistance.

[0203] <Self-repair test> "Breaking strength TB (MPa)" was measured by conducting a tensile test on an ASTM D638 Type V shaped test piece with a thickness of approximately 2 mm in accordance with JIS K 6251 "Vulcanized rubber and thermoplastic rubber - Determination of tensile test characteristics" at an atmosphere of 23°C and a tensile speed of 5 mm / sec. The "TB repair rate (%)" is a value defined as "TB (MPa) of repaired test piece / TB (MPa) of annealed test piece x 100." Here, the repaired test piece is a test piece obtained by cutting the test piece for measuring the breaking strength TB (MPa) in the thickness direction at the center of its long side, immediately bonding the cut surfaces together, and then heat-treating at 80°C for 24 hours. The annealed test piece is a test piece obtained by heat-treating the test piece for measuring the breaking strength TB (MPa) at 80°C for 24 hours.

[0204] <Preparation of test tires> According to the composition shown in Table 2, materials other than sulfur and vulcanization accelerator are kneaded for 5 minutes at 150° C. using a 1.7 L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Sulfur and a vulcanization accelerator are added to the kneaded mixture, and the mixture is kneaded for 5 minutes at 80° C. using an open roll to obtain an unvulcanized rubber composition. The unvulcanized rubber composition is molded into the shape of a cap tread, and is laminated together with other tire components on a tire building machine to form an unvulcanized tire. The unvulcanized tire is then vulcanized at 170°C for 10 minutes to produce a test tire (size 205 / 70R15, passenger car tire).

[0205] [Table 2]

[0206] The present invention (1) is a tire having a tire member made of a rubber composition containing a rubber component and an ethylene-anisylpropylene copolymer, The copolymer is a block copolymer consisting of a soft segment block and a hard segment block, the soft segment is composed of an alternating sequence of ethylene and anisylpropylene, and the total proportion of the structural units of the soft segment is 60 mol % or more of the total structural units of the copolymer; The hard segment is made of polyethylene, The copolymer has a number average molecular weight of 3,000 or more and 700,000 or less, A tire that satisfies the following formula (1). The content of the rubber component in the rubber composition [mass%] / the content of the copolymer in the rubber composition [mass%] > 1.0 (1)

[0207] The present invention (2) is the tire according to the present invention (1), which satisfies the following formula (2). The content of the rubber in the rubber composition [mass%] / the content of the copolymer in the rubber composition [mass%]>2.0 (2)

[0208] The present invention (3) is the tire according to the present invention (1), which satisfies the following formula (3). The content of the rubber in the rubber composition [mass%] / the content of the copolymer in the rubber composition [mass%]>3.0 (3)

[0209] The present invention (4) is a tire in any combination with any of the present inventions (1) to (3), wherein in the rubber composition, the average domain diameter of the copolymer is 10 nm or more and 10 μm or less.

[0210] The present invention (5) is a tire in any combination with any of the present inventions (1) to (4), in which the rubber composition further contains a filler and satisfies the following formula (4): The content of the rubber component in the rubber composition [mass%] / the content of the filler in the rubber composition [mass%] > 1.0 (4)

[0211] The present invention (6) is the tire according to the present invention (5), which satisfies the following formula (5). The content of the rubber component in the rubber composition [mass%] / the content of the filler in the rubber composition [mass%] > 1.2 (5)

[0212] The present invention (7) is a tire in any combination with any of the present inventions (1) to (6), wherein the tire component has a maximum thickness of 0.2 mm or more.

[0213] The present invention (8) is a tire in any combination with any of the present inventions (1) to (6), wherein the tire component has a maximum thickness of 1.0 mm or more.

[0214] The present invention (9) is a tire that satisfies the following formula (6) and is optionally combined with any of the present inventions (1) to (8). A content of the copolymer in the rubber composition [mass%] / maximum thickness of the tire component [mm]<15 (6)

[0215] The present invention (10) is a tire that satisfies the following formula (7) and is optionally combined with any of the present inventions (1) to (8). A content of the copolymer in the rubber composition [mass%] / maximum thickness of the tire component [mm]<10 (7)

[0216] The present invention (11) is a tire that satisfies the following formula (8) and is optionally combined with any of the present inventions (1) to (8). A content of the copolymer in the rubber composition [mass%] / maximum thickness of the tire component [mm]<5 (8)

[0217] The present invention (12) further provides a tire member comprising a tread, The tire is any combination with any of the present inventions (1) to (11), wherein the groove depth of the circumferential groove formed in the tread is 2.0 mm or more and 20.0 mm or less.

[0218] The present invention (13) is the tire according to the present invention (12), which satisfies the following formula (9). The content of the copolymer in the rubber composition [mass%] / the groove depth [mm]<10 (9)

[0219] The present invention (14) is the tire according to the present invention (12), which satisfies the following formula (10). The content of the copolymer in the rubber composition [mass%] / the groove depth [mm]<5 (10)

[0220] The present invention (15) is the tire according to the present invention (12), which satisfies the following formula (11). The content of the copolymer in the rubber composition [mass%] / the groove depth [mm]<3 (11) [Explanation of symbols]

[0221] 2 Tires 4 Tread 6 Sidewall 8 Wing 10 Clinch 12 Beads 14 Carcass 16 Belt Layer 18 Bands 20 Inner Liner 22 Chafer 24 Tread surface 26 Groove 28 Base Layer 30 Cap Layer 32 Bead core 34 Bead Apex 36 Carcass ply 36a Main part 36b Folded part 38 Inner layer 40 outer layer 42 Main groove 44 Ribs CL Tire equatorial plane P is a point on the tread surface T Thickness of tread 4 at point P D: Depth of the circumferential main groove formed in the tread

Claims

1. A tire having a tire member made of a rubber composition containing a rubber component and an ethylene-anisylpropylene copolymer, The copolymer is a block copolymer consisting of a soft segment block and a hard segment block, the soft segment is composed of ethylene and anisylpropylene linked alternately, and the total proportion of the structural units of the soft segment accounts for 60 mol % or more of the total structural units of the copolymer; The hard segment is made of polyethylene, The copolymer has a number average molecular weight of 3,000 or more and 700,000 or less, A tire that satisfies the following formula (1). The content of the rubber component in the rubber composition [mass%] / the content of the copolymer in the rubber composition [mass%] > 1.0 (1)

2. The tire according to claim 1, which satisfies the following formula (2). The content of the rubber in the rubber composition [mass%] / the content of the copolymer in the rubber composition [mass%] > 2.0 (2)

3. The tire according to claim 1, which satisfies the following formula (3). The content of the rubber in the rubber composition [mass%] / the content of the copolymer in the rubber composition [mass%] > 3.0 (3)

4. The tire according to claim 1 , wherein in the rubber composition, the average domain diameter of the copolymer is 10 nm or more and 10 μm or less.

5. The tire according to claim 1 , wherein the rubber composition further contains a filler and satisfies the following formula (4): The content of the rubber component in the rubber composition [mass%] / the content of the filler in the rubber composition [mass%] > 1.0 (4)

6. The tire according to claim 5, which satisfies the following formula (5). The content [mass%] of the rubber component in the rubber composition / the content [mass%] of the filler in the rubber composition > 1.2 (5)

7. The tire according to claim 1 , wherein the tire component has a maximum thickness of 0.2 mm or more.

8. The tire according to claim 1 , wherein the tire component has a maximum thickness of 1.0 mm or more.

9. The tire according to claim 1, which satisfies the following formula (6). A content of the copolymer in the rubber composition [mass%] / maximum thickness of the tire member [mm] < 15 (6)

10. The tire according to claim 1, which satisfies the following formula (7). A content of the copolymer in the rubber composition [mass%] / maximum thickness of the tire member [mm] < 10 (7)

11. The tire according to claim 1, which satisfies the following formula (8). A content of the copolymer in the rubber composition [mass%] / maximum thickness of the tire member [mm] < 5 (8)

12. The tire component is a tread, The tire according to claim 1, wherein a groove depth of the circumferential groove formed in the tread is equal to or greater than 2.0 mm and equal to or less than 20.0 mm.

13. The tire according to claim 12, which satisfies the following formula (9). The content of the copolymer in the rubber composition [mass%] / the groove depth [mm] < 10 (9)

14. The tire according to claim 12, which satisfies the following formula (10). The content of the copolymer in the rubber composition [mass%] / the groove depth [mm] < 5 (10)

15. The tire according to claim 12, which satisfies the following formula (11). The content of the copolymer in the rubber composition [mass%] / the groove depth [mm]<3 (11)